Efeito da insularização florestal sobre a sinalização acústica de aves na Amazônia - Schunemann, Vítor (Instituto Nacional de Pesquisas da Amazônia - INPA, 2024)
Artificially insularized forests are profoundly altered not only in terms of biota composition and the physical structure of the environment but also in the configuration of their acoustic landscapes. However, studies on this landscape reconfiguration over spectral properties of acoustic signaling in species, especially over broad temporal scales, are limited to a few species. Through passive acoustic monitoring, combined with automated detection supervised by an ornithologist, we tested the general hypothesis that structural characteristics of insularized forests — island area and tree structure — affect a spectral acoustic parameter relevant for intra- and interspecific communication in birds: the peak frequency of vocalization. For this, we related acoustic data from 28 bird species with environmental variables across 75 sampling units in the region of the Balbina Hydroelectric Plant Lake, Central Amazonia, 28 years after its formation. The accuracy of the spectral data obtained through autonomous recorders was corroborated by the pronounced negative relationship between body mass and peak vocalization frequency of the species. The structural characteristics of the insularized forests did not affect the vocalization of 75% of the considered bird species. The exceptions when analyzing the effect of area on peak frequency are Certhiasomus stictolaemus and Tolmomyias poliocephalus, presenting increase in frequency, and Hypocnemis cantator, presenting decrease in frequency as the area increases. For tree cover, the species that were exceptions are Dendrocolaptes certhia, Leptotila rufaxilla, and Monasa atra, which presented increase in frequency, while Myiarchus ferox presented decrease in frequency as the cover increased. Our results indicate that, despite the extensive literature documenting the adverse effects of the formation of the Balbina Hydroelectric Plant Lake on various facets of biodiversity, the spectral properties of the acoustic signaling of birds, with few exceptions, have not changed after 28 years of landscape insularization. The results presented here constitute an important baseline for long-term investigations on this topic. Keywords: Acoustic Adaptation Hypothesis, Animal Behavior, Arbimon, Autonomous Recording, Insularization
Keywords: Ecologia Comportamental; Bioacústica